The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1577/t05-116.1
|View full text |Cite
|
Sign up to set email alerts
|

Allozyme and Microsatellite DNA Analyses of Lingcod from Puget Sound, Washington, and Adjoining Waters

Abstract: In all, 472 lingcod Ophiodon elongatus from six areas of Puget Sound, the Strait of Juan de Fuca, and the outer coast of Washington were assayed for 44 allozyme and 9 microsatellite DNA loci to investigate possible population subdivision. Levels of genetic variation at many of the allozyme loci and all of the microsatellite DNA loci were reasonably high, and there was no evidence of significant Hardy-Weinberg or linkage disequilibrium. Pairwise genotypic tests of population differentiation showed no evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 16 publications
0
8
1
Order By: Relevance
“…In this study, we identify two distinct genetic clusters of lingcod showing a latitudinal cline in the Eastern Pacific, with a genetic break centered off Northern California between Stewarts Point and Point Reyes. This novel delineation of population boundaries differs from previous lingcod population genetic studies, which have generally suggested coastwide panmixia (Jagielo et al., 1996; LeClair et al., 2006; Marko et al., 2007). Compared to the single mitochondrial sequence or 19–32 nuclear markers used in these prior studies, the sampling of more sites across the genome with >16,000 SNPs empowered the ability to detect this signal of population structure.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…In this study, we identify two distinct genetic clusters of lingcod showing a latitudinal cline in the Eastern Pacific, with a genetic break centered off Northern California between Stewarts Point and Point Reyes. This novel delineation of population boundaries differs from previous lingcod population genetic studies, which have generally suggested coastwide panmixia (Jagielo et al., 1996; LeClair et al., 2006; Marko et al., 2007). Compared to the single mitochondrial sequence or 19–32 nuclear markers used in these prior studies, the sampling of more sites across the genome with >16,000 SNPs empowered the ability to detect this signal of population structure.…”
Section: Discussioncontrasting
confidence: 76%
“…(1996) and LeClair et al. (2006) used allozyme or allozyme and microsatellite markers, respectively, which sample less than a few dozen sites in the nuclear genome, while Marko et al. (2007) specifically evaluated population structure using cytochrome oxidase I in the mitochondrial genome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We therefore used two sources of information on population status from a Washington-Oregon coastal stock assessment for lingcod: (1) estimated spawning stock biomass, 1950-2009, and (2) catch per unit effort indices from commercial trawl fishery logbook and fish ticket data, 1976-1997(Hamel et al 2009). These indices may be a reasonable proxy for patterns in Puget Sound populations given limited genetic differentiation between lingcod in the inland waters and those on the outer coast of Washington (LeClair et al 2006). In contrast, rockfish populations in Puget Sound are genetically, demographically, and ecologically distinct from coastal stocks (Drake et al 2010); stock assessments or survey time series were not available for Puget Sound rockfishes.…”
Section: Comparison Between Interview and Biological Assessment Datamentioning
confidence: 99%